Carbon Sequestration: Status of Sequestered Soil Organic Carbon under Different land uses in Jhalawar District of Rajasthan - Sharma, Himani; Gupta, M. K.; Chauhan, P. S. (Indian Forester, 2014)
A study was carried out to generate the information on organic carbon stored in the soils of four land uses viz. Forests, Grassland, Barren Land and Agriculture in Jhalawar district of Rajasthan. Under the forest land lise, maximum SOC pool (11.75 t/ha) was under Anogeissus pendu/a followed by Diospyros me/anoxy/on (9.99 t/ha), Lannea coromande/ica (8.92 t/ha), Butea monosperma (8.81 t/ha), miscellaneous (8.74 t/ha), Tectona grandis (7.03 t/ha), and the least was under Termina/ia arjuna (6.78 t/ha). Grass land site was situated on slope terrain and samples were collected from top of the slope and bottom of the slope. Higher SOC pool (6.13 t/ hal was observed at the bottom while on top SOC pool was lesser (2.90 t/ha). SOC pool in the barren land of the Jhalawar district was 3.18 t/ha which is quite low. SOC pool under agriculture was 2.47 t /ha in the district. When SOC pool under all the land uses of Jhalawar district were integrated, it was observed that forests contribute the maximum share (47.12 %) of the total SOC pool followed by grasslands (23.66 %), barren land (16.65 %), and the least was agriculture (12.57 %).